The degree of Disposition Effect amongst Indians - Sakhlecha, Rishabh (2013)
The disposition effect, which was first introduced by Shefrin and Statman (1985), refers to the tendency of individuals to profit their gaining transactions (winners) too early and the reluctance to realize their losing transactions (losers). In other words, the tendency for individuals to demonstrate reluctance in realizing losses and eagerness to realize gains is termed as disposition effect. The main purpose of this paper is to analyze the degree of disposition effect amongst Indians. To measure this effect a computer programme was developed on Microsoft Excel which simulates the stock market. An experiment was carried out in India in the summer of 2013 to measure the disposition effect amongst the participants. The participants for the experiment comprised of thirty university students who had taken up finance as a subject in their studies in the past. To measure the disposition effect, this paper follows the measure used by Weber and Camerer (1998), which considers the difference between the number of trades with realized gains by an investor and the number of trades with realized losses relative to the number of all trades to estimate the disposition effect. The main findings of the experiment were as follows: First, individuals revealed risk averse attributes for gains and losses, but the risk averse magnitude for gains was larger than it was for losses. In other words individuals realized more gains than they realized their losses. Second, participants who had just completed their undergraduate studies displayed a higher disposition effect as compared to participants who had completed their masters. Finally, females were found to be more risk averse than males.